Characteristics and Correlates of Lifetime Suicidal Thoughts and Attempts Among Young Black Men Who Have Sex With Men (MSM) and Transgender Women. (April 2018) - Wilton, Leo; Chiasson, Mary Ann; Nandi, Vijay; Lelutiu-Weinberger, Corina; Frye, Victoria; Hirshfield, Sabina; Hoover, Donald R.; Downing, Martin J.; Lucy, Debbie; Usher, DaShawn; Koblin, Beryl
This study examined characteristics and correlates of lifetime suicidal thoughts and suicide attempts among HIV-negative young Black men who have sex with men (MSM) and transgender women (transwomen) between 16 and 29 years of age ( N = 161). In our sample, 36.6% of young Black MSM and transwomen reported a history of lifetime suicidal thoughts, while 16.1% reported prior suicide attempts. Using multivariable analysis, a history of intimate partner violence, greater psychological distress, and higher perceived sexuality discrimination were significantly associated with lifetime suicidal thoughts. Childhood sexual abuse history, greater psychological distress, lower score for outness, and higher perceived sexuality discrimination were significantly related to suicide attempts among young Black MSM and transwomen. Efforts to identify and understand factors associated with lifetime suicidal thoughts and attempts are urgently needed to inform the development and implementation of culturally relevant mental health prevention strategies for young Black MSM and transwomen.